Silencing ZIC5 suppresses glycolysis and promotes disulfidptosis in lung adenocarcinoma cells - Cimei Zeng; Denggao Huang; Lei Wang; Haimei Liang; Ximiao Ma (Cancer Biology & Therapy)
Objective This study aims to explore the effects of silencing Zic family member 5 (ZIC5) on glucose metabolism and disulfidptosis in lung adenocarcinoma (LUAD) cells.Methods Data from The Cancer Genome Atlas (TCGA) was used to analyze ZIC5 expression in LUAD and its association with patient outcomes. ZIC5 was silenced in A549 and H1299 cells using siRNA. The expression of ZIC5 mRNA and protein was assessed by qRT-PCR and Western blot. Cell proliferation was evaluated through CCK-8 and 5-ethynyl-2’-deoxyuridine (EdU) assays, while glucose uptake, lactate production, and ATP levels were measured to assess energy metabolism. Seahorse XF analysis was used to evaluate extracellular acidification rate (ECAR) and oxygen consumption rate (OCR). Disulfidptosis was assessed through NADP+/NADPH ratio, glutathione (GSH) content, GSSG/GSH ratio, and immunofluorescence staining.Results ZIC5 is highly expressed in LUAD and is associated with poor patient prognosis. Silencing ZIC5 significantly reduced its mRNA and protein levels in A549 and H1299 cells, markedly inhibited cell proliferation, and led to significant decreases in glucose uptake, lactate production, ATP levels, ECAR, and OCR. Additionally, silencing ZIC5 resulted in an increased NADP+/NADPH ratio, decreased GSH levels, and a reduced GSSG/GSH ratio, alongside classic disulfidptosis features.Conclusion ZIC5 plays a crucial role in promoting LUAD cell proliferation and energy metabolism while inhibiting disulfidptosis. Silencing ZIC5 markedly suppresses these processes, indicating its potential as a therapeutic target in LUAD.